Street Health: Cross-sectional study identifying social medicine issues amongst patients of the Health Center for Homeless in Berlin, Germany - Peter Tinnemann; Theresa E. S. Bauer; Jenny de la Torre Castro; Silvia Binting; Thomas Keil (Social Medicine Publication Group, 2013)
Background: An estimated 265,000 people are homeless in Germany, with 10,000 in Berlin alone. Their physical and psychological health is particularly threatened by their living conditions. Access to health services is often difficult, sometimes impossible, for them. New approaches to care of the homeless offer multidisciplinary support, but systematic analysis of these are lacking. The aim of this study is to analyze socio-demographic and health characteristics of patients at the Berlin Health Center for Homeless (Gesundheitszentrum für Obdachlose), founded in 2006. Methods: Retrospective analysis of primary care patient data from September 2006 to March 2008 regarding reasons for seeking care, existing health problems, and socio-demographic characteristics. Results: Among a total of 440 homeless patients, 81% were male, with a mean age of 43.5 years (SD=13), 19% were female, with a mean age of 37.2 years (SD=12.8), 62% were single, 26% were foreigners (particularly from Eastern Europe), 71% had obtained a graduation certificate after at least 10 years of schooling, 16% had higher education, and 53% were without health insurance. 58% had a tobacco addiction and 43% an alcohol addiction. The most frequent health complaints were infectious diseases (16%), trauma (15%), respiratory diseases (14%), and skin diseases (9%). Conclusions: Despite popular perceptions, homelessness in Berlin increasingly affects women, young adults, and better-educated patients. More systematic and longitudinal studies analyzing specific medical care for the homeless are urgently needed.